IRF7-Dependent Type I Interferon Production Induces Lethal Immune-Mediated Disease in STAT1 Knockout Mice Infected with Lymphocytic Choriomeningitis Virus - Li, Wen (American Society for Microbiology, 2014)
Following systemic infection with lymphocytic choriomeningitis virus (LCMV), STAT1 knockout (KO) mice but not wild-type, STAT2 KO, IRF9 KO, or IFNAR KO mice develop lethal disease perpetrated by CD4(+) T cells. IRF7 is a key transcriptional activator of type I IFN (IFN-I) during LCMV infection. Here, the role of IRF7 in the lethal host response to LCMV infection in STAT1 KO mice was examined. In contrast to STAT1 KO mice, STAT1/IRF7 double KO (DKO) mice survived LCMV infection with a reduced immune pathology in key organs, such as the liver and spleen. However, similar to STAT1 KO mice, STAT1/IRF7 DKO mice failed to control LCMV replication and spread. LCMV infection in STAT1 KO mice was associated with a significant elevation in the levels of a number of cytokines in serum, including IFN-Is, but this was largely absent in STAT1/IRF7 DKO mice, which had a modest increase in the levels of gamma interferon and CCL2 only. Since IRF7 is known to be a key transcriptional regulator of IFN-I gene expression, the possible role of IFN-I in lethal disease was examined further. STAT1/IFNAR DKO mice, in contrast to STAT1 KO mice, all survived infection with LCMV and exhibited little tissue immune pathology. Additionally, STAT1 KO mice that were deficient for either of the two IFN-I signaling molecules, STAT2 or IRF9, also survived LCMV infection. We conclude that the lethal immune-mediated disease resulting from LCMV infection in STAT1 KO mice is (i) dependent on IRF7-induced IFN-I production and (ii) driven by noncanonical IFN-I signaling via STAT2 and IRF9. IMPORTANCE Here we report on the basis for the novel, fatal immune-mediated disease of STAT1 KO mice infected with LCMV. Our findings show that, surprisingly, the pathogenesis of this disease is dependent on IRF7-mediated type I interferon production. Moreover, our study identifies noncanonical type I interferon signaling via STAT2 and IRF9 to be essential for the type I IFN-driven fatal disease in LCMV-infected STAT1 KO mice. These results further highlight the significance of noncanonical type I IFN signaling in the pathogenesis of host-mediated injury following viral infection.